Urban battle command in the twenty-first century - Glenn, Russell W. (RAND, 2005)
Urban areas are notorious for complicating operational planning, command, control, and the communications that facilitate the three. Frequent interruptions of line of sight due to the prolificacy of man-made structures interfere with radio and global positioning system signals. They often combine with extreme noise, dust, smoke, and light conditions to impede leader control at all echelons. The density of noncombatants and their potentially crucial influence on friendly force success further demand effective employment and synchronization of psychological operations, civil affairs, public affairs, and other resources. Savvy use of existent systems, employing decentralized control procedures, and innovation all have their place in overcoming these inherent limitations in the service of achieving objectives across the spectrum of conflict.